Fast 1.5 T chest MRI for the assessment of interstitial lung disease extent secondary to systemic sclerosis. Issue 9 (September 2016) - Pinal-Fernandez, Iago; Pineda-Sanchez, Victor; Pallisa-Nuñez, Esther; Simeon-Aznar, Carmen; Selva-O'Callaghan, Albert; Fonollosa-Pla, Vicente; Vilardell-Tarres, Miquel
Abstract This study aims to evaluate the utility of magnetic resonance imaging (MRI) to assess interstitial lung disease (ILD) extent in patients with systemic sclerosis (SSc). Patients with SSc and varying degrees of ILD with a high-resolution computed tomography (HRCT), pulmonary function tests (PFTs), and a chest MRI containing an ultrafast SE sequence performed less than 1 year apart were included in the study. Wells global disease extent and Goh's staging algorithm were used to measure and categorize ILD both for MRI and HRCT. Correlation and diagnostic performance of MRI compared with HRCT and PFTs were calculated. Eighteen SSc patients were studied. MRI showed a good performance to detect ILD (AUC = 0.96) and was correlated with forced vital capacity (r  = −0.60, p  = 0.01), diffusing capacity of the lung for carbon monoxide (r  = −0.79, p  = 0.04), and also with HRCT (r  = 0.85, p  < 0.001), but MRI extent values were consistently lower than HRCT and, thus, not directly comparable. Goh's algorithm using HRCT and transformed to be used with MRI showed a good agreement (kappa = 0.73, p  < 0.001) and MRI-measured ILD extent presented good intra-observer (ICC = 0.86) and inter-observer (ICC = 0.90) reliability. In SSc patients, MRI proved to be a good technique to detect and categorize ILD extent compared with HRCT, suggesting that it may be a valuable x-ray sparing technique for selected cases.